Measurement complexity of adherence to medication - Galato D; Schuelter-Trevisol F; Piovezan AP (Dove Medical Press, 2012)
Dayani Galato, Fabiana Schuelter-Trevisol, Anna Paula PiovezanMaster Program in Health Sciences, University of Southern Santa Catarina (Unisul) Tubarão, Santa Catarina, BrazilAdherence to pharmacologic therapy is a major challenge for the rational use of medicines, particularly when it comes to antiretroviral drugs that require adherence to at least 95% of prescribed doses.1 Studies in this area are always important and contribute to medication adherence understanding, even though there is no reference test for measuring this. Recently, an article was published in this journal that proposes the determination of lamivudine plasma concentration to validate patient self-reported adherence to antiretroviral treatment.2 In that study, serum levels obtained after 3 hours of ingestion of the last dose of the drug were compared with patient reports that were classified into different levels of adherence, based on their recall of missed doses in the previous 7 days.It was hypothesized by the authors that the use of a biological marker for drug adherence was extremely important, given the relevance of the topic. However, we would like to draw attention to some points that may determine the success of the use of similar methods for this purpose. The formation of groups with similar anthropometric characteristics is relevant since the dose of lamivudine may have to be changed, depending, for example, on sex, weight, and age.3 Even information considered important by the authors of that study was not provided. There is a need for greater clarity on the eligibility criteria, especially with regard to the clinical stage of the disease, CD4 counts and viral load, associated diseases, and comorbidity, as well as the evaluation of kidney function and other medications used that can affect lamivudine pharmacokinetics.3View original paper by Minzi and colleagues